AN ANALYSIS OF LANGUAGE STYLE IN TAYLOR SWIFT'S SPEECH AT NEW YORK UNIVERSITY'S CLASS OF 2022 - Fitria Sari, Sinawang Deka; Wulandari, Sri; Entusiastik, Entusiastik (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
Language style can be seen in particular language forms, such as variation, style of language, or dialect, and its application in society. Researchers are interested in researching language style because each individual has their style of speech. When Taylor Swift spoke, she did not read the script but spoke spontaneously. Therefore, this study's purpose is to analyze the type of language style and the dominant language style used by Taylor Swift in her speech at New York University on the day of her doctoral graduation. This study uses descriptive qualitative research methods. The data obtained came from the official New York University YouTube channel as the primary source and speech transcripts from the official billboard music web page. In this study, researchers used the leading theory, namely Martin Joos (1967). Therefore, it can be concluded that the casual style is the most common because it tends to lead to the life story of Taylor Swift so that the language used tends to be relaxed, which is presented in an easy-to-understand language such as daily English.